Further exploration on causes of temperature anomalies associated with the abnormal northern annular mode - Suo LingLing; Tan BenKui; Huang JiaYou (Science Bulletin, 2009)
This article concerns the temperature anomalies during the high index phase of the northern annual mode for the wintertime from January to March. The response of the zonal and meridional winds and the temperature advection caused by the anomalous horizontal wind are investigated. The results show that both the zonal and meridional winds experience strong anomalies and the temperature advection induced by both the anomalous zonal and meridional winds is responsible for the temperature anomalies associated with the high index northern annual mode. The temperature advection induced by the anomalous zonal wind contributes dominantly to the cooling in the Atlantic and the Bering Sea while the temperature advection induced by the anomalous merional wind contributes dominantly the warming in the United States of America and the cooling in southern Europe and Canada. The superposed influences caused the obvious warming in north Eurasia. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000267145500018&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Multidisciplinary Sciences SCI(E) 4 ARTICLE 12 2101-2106 54